POTENSI PRODUKSI TANAMAN PORANG (Amorphophallus muelleri Blume) DI KELOMPOK TANI MPSDH WONO LESTARI DESA PADAS KECAMATAN DAGANGAN KABUPATEN MADIUN. - Rofikhoh, Kusnul; Setiahadi, Rahmanta; Rekyani Puspitawati, Indah; Lukito, Martin (JURNAL AGRI-TEK, 2016)
Porang plant (Amorphophallus muelleri Blume) known as iles-iles plant is a shrub that has a height of 100-150 cm, erect stems, soft, smooth stems are green or black mottled white. This study aims to determine the factors that affect crop production potential porang, research carried out in the village Padas District of Madiun. The research method used is descriptive and qualitative research that lead to the disclosure of a problem or situation as it is and reveal the facts on the ground, including seeds, maintenance, fertilizing and harvesting. With the number of respondents as many as 25 people at random from the Farmers Group MPSDH Wono Lestari in Village Padas District of Madiun This Research aims to determine cultivation porang in Farmers MPSDH Wono Lestari Village Padas District of Madiun in increasing crop production potential porang Results research shows the potential for production in Farmers MPSDH Wono Lestari very good for cultivation porang. Porang crop production potential is influenced by factors: Good seed, Maintenance with weeding, fertilization with manure and harvest excavated using a hoe. Results of treatment A.1 to A.8 and B.1 to B.8 show A.1 treatment are: tuber frog (bubil), manual weeding with a hoe tool use and sickle and fertilization is done without the use of chemicals and fertilizers with goat manure and compost that harvest done porang farmers dug with picks, superior to treatment until A.8 A.2 and B.1 to B.8 when seen from the number of tuber yield porang.Keywords: Potential Production, MPSDHFarmers. Group,